Analysis of the Influence of Profitability and Ownership Structure on the Timeliness of Financial Reporting in Healthcare Companies Listed on the Indonesian Stock Exchange - Mediaty, Mediaty; Anto, Fitri Anto; Hamid Habbe, Abdul (Journal of Law and Social Politics, 2024)
The purpose of this study was to evaluate the impact of profitability and ownership structure on the timeliness of financial reporting of Healthcare companies listed on the Indonesia Stock Exchange. The study used the purposive sampling method to sample 20 Healthcare companies that were consistently listed on the Indonesia Stock Exchange during 2020. Furthermore, profitability variables and ownership structure were tested using logistic regression at a 5% significance level. Findings from the research hypothesis suggest that profitability has a significant influence on the timeliness of reporting, while ownership structure has no significant influence on the timeliness of corporate financial reporting.